Influence of Large-scale Foundation Pit Sloping Excavation on Adjacent Operating Metro Tunnel and Actual Measurement Analysis - YANG Ge; DUAN Luo; HUANG Tong; XU Qianwei; CUI Yuebang (Chengshi guidao jiaotong yanjiu, 2024)
Objective There are complex coupling effects between foundation pit and tunnel due to different construction processes. The foundation pit construction will inevitably cause disturbance to the existing operation tunnel, leading to displacement of the tunnel and even affecting its operation safety in serious cases. Therefore, it is necessary to study proper foundation pit excavation methods and excavation steps to reduce the excavation influence on the existing adjacent tunnel. Method Based on a sunken plaza foundation pit, the finite element numerical simulation is used to study four excavation conditions of the foundation pit adjacent to the existing tunnel. The distribution pattern of the tunnel internal force and the tunnel displacement trend as well as the deformation characteristics of the stratum under different excavation methods and steps are analyzed,and the effects of different working conditions on the tunnel deformation during excavation are compared. The results are verified and analyzed in combination with the actual monitored on-site data during the foundation pit excavation. Result & Conclusion Compared with the trenching excavation, the ordinary slope excavation causes less vertical tunnel deformation. Compared with the layered excavation, the continuous excavation induces less vertical deformation. The final vertical deformations of the tunnel under different steps are close to each other. Compared with continuous excavation, the layered excavation causes larger tunnel horizontal deformation, mainly resulting from multiple excavation steps and notable spatial and temporal effect of the foundation pit. According to the actual monitored on-site data, the vertical and horizontal deformations of the tunnel and the relative vertical deformation of the track present a trend of first increasing and then decreasing during construction.